The effect of topical cyclopentolate on anterior segment parameters in patients with keratoconus - Kırgız, Ahmet; Karaman Erdur, Sevil; Çakmak, Semih; Dikkaya, Funda; Aydın, Rukiye (Turkish Ophthalmological Society, 2020)
Objectives: To investigate the effect of cycloplegia on anterior segment structures in keratoconus and forme fruste keratoconus patients using corneal topography.Materials and Methods: In this study, 40 patients with keratoconus (group 1), 40 patients with forme fruste keratoconus (group 2), and 40 healthy subjects (group 3) were evaluated prospectively. Flat keratometry (K) value (K1), steep K value (K2), mean K value (Kmean), maximum K value (Kmax), corneal astigmatism value, anterior chamber depth (ACD), symmetry index front, symmetry index back, thinnest corneal thickness, central corneal thickness and corneal volume were measured using Sirius topography before and after cycloplegia. Results were compared with one way ANOVA test.Results: The mean age of the participants was 24.4 +/- 6.2 years for group 1, 26.3 +/- 4.3 years for group 2 and 26.5 +/- 6.1 years for group 3. There was no difference between the groups with respect to mean age and gender (p>0.05). Mean K1 value was 45.54 +/- 2.43 diopters (D) before cycloplegia and 45.46 +/- 2.48 D after cycloplegia for group 1(p=0.044). K1 value didn't change significantly after cycloplegia for group 2 and 3 (p=0.275, p=0.371). There was no significant difference in K2 and Kmean values after cycloplegia for all groups (p>0.05). Kmax value decreased significantly after cycloplegia in group 1 (p=0.001), but the difference was not significant for group 2 and 3 (p=0.087, p=0.241). ACD increased significantly after cycloplegia in all groups (p=0.001).Conclusion: Cycloplegia causes corneal flattening only in manifest keratoconus patients, leading to an increase in ACD in all groups.

Amaç: Sikloplejinin keratokonus ve forme fruste keratokonuslu olgularda ön segment yapıları üzerine etkisini kornea topografisi ile değerlendirmektir. Gereç ve Yöntem: Çalışma kapsamında 40 keratokonus (grup 1), 40 forme fruste keratokonus (grup 2) ve 40 sağlıklı olgunun (grup 3) birer gözü prospektif olarak değerlendirildi. Siklopleji öncesi ve sonrasında Sirius topografi cihazı ile düz keratometri (K) değeri (K1), dik K değeri (K2), ortalama K değeri (Kort), maksimum K değeri (Kmaks), korneal astigmatizma değeri, ön kamara derinliği (ÖKD), ön simetri indeksi, arka simetri indeksi, en ince korneal kalınlık, merkezi kornea kalınlığı ve kornea volümü değerleri ölçüldü. Sonuçlartek yönlü varyans analizi testi ile karşılaştırıldı. Bulgular: Yaş ortalaması grup 1’de 24,4±6,2 yıl; grup 2’de 26,3±4,3 yıl; grup 3’te 26,5±6,1 yıl idi. Gruplar arasında yaş ve cinsiyet açısından anlamlı bir fark yoktu (p>0,05). Grup 1’de siklopleji öncesi ortalama K1 değeri 45,54±2,43 diyoptri (D) iken siklopleji sonrasında 45,46±2,48 D idi (p=0,044). Grup 2 ve 3’te siklopleji sonrasında K1 değerinde anlamlı bir değişiklik bulunmadı (p=0,275, p=0,371 sırasıyla). Her üç grupta da siklopleji sonrasında K2 ve Kort değerlerinde anlamlı bir değişim izlenmedi (p>0,05). Kmaks değerlerinde siklopleji sonrasında grup 1’de anlamlı azalma olurken (p=0,001), grup 2 ve grup 3’te anlamlı değişiklik izlenmedi (p=0,087, p=0,241 sırasıyla). Üç grupta da siklopleji sonrasında ÖKD’de istatistiksel anlamlı artış izlendi (p=0,001). Sonuç: Siklopleji sadece belirgin keratokonus hastalarında korneada düzleşmeye neden olurken, tüm gruplarda ÖKD’de artışa yol açmaktadır.
Keratokonus hastalarında topikal siklopentolatın ön segment parametreleri üzerine etkisi
Keywords: Cyclopentolate; Keratoconus; Cornea; Corneal Topography; Anterior Chamber; Siklopentolat; Keratokonus; Kornea; Korneal Topografi; Ön Kamara